Fluidization bed coating of copper bars with epoxy powder - Soh, Chiaw Min (2014)
Fluidized bed coating (FBC) is a process where preheated material is dipped into a flowing liquid bed of powder. Although FBC has existed for more than half a century, however there is little knowledge about the fluidized bed design that gives excellent fluidization quality as well as reducing powder entrainment. The objectives of this thesis are to investigate the effect of two different types of distributor with different pressure drop on powder coating, hydrodynamics of fluidized bed coating process, and effect of flow rate on powder coating quality such as thickness, uniformity, reduced entrainment and current leakage. The understanding and research finding is the key to the design of an industrial scale fluidized bed powder coater. A pilot fluidized bed coater was designed and built to run the experimental work for the study on pressure drops and also coating experiments using epoxy powder on copper bars. Pure copper bars with a purity of 99.99% were used for coating. The quality of the coated samples such as the coating thickness and current leakage were evaluated. Continuous and repetitive dipping method was experimented to study on the coating thickness at different processing time. At a continuous dipping of 14 seconds, and with air flow rates of 3 LPM, 8 LPM and 12 LPM, the coating thickness achieved were 1079.2 μm, 1275.8 μm and 659.2 μm respectively. Using repetitive method, overall coating thickness is lower than continuous coating at the same dipping time. The current leakage shows that low air flow rate for continuous dipping method has the lowest current leakage at the similar coating thickness at 720 μm compared to repetitive dipping method. Its leakage is 0.53 mA compared to normal air flow rate at 0.68 mA and high air flow rate at 0.75 mA. Different dipping methods were studied to understand the difference between continuous dipping and repetitive dipping on the coating uniformity on the bar. It was found that continuous dipping gave a more uneven coating on the samples which can be observed through the large standard deviation error bar. Further study on the effect of different air distributor pressure drops was also carried out. Theoretically the pressure drop of distributor ratio against the bed height should be in the range of 0.1 to 0.3 to ensure a good bed rise with few bubbles. It was found that distributor B with a higher bed height of 0.3 m gave a ratio within this range as compared to distributor A where only 0.2 m and 0.15 m bed height that gave the similar ratio.